Arbuscular Mycorrhizal Fungi and Higher Plants Fundamentals and Applications - Ahammed, Golam Jalal; Hajiboland, Roghieh; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This book covers the fundamentals of arbuscular mycorrhizal fungi (AMF) and higher plant symbiosis with potential implications in crop production. It provides new insights into our understanding of the mechanisms of AMF-mediated plant growth regulation and stress tolerance covering the most recent biochemical, physiological, molecular, environmental, and ecological studies. Focusing on AMF-induced physiological and molecular mechanisms of enhanced tolerance to stress, environmental stress is discussed in several dedicated chapters. The book provides not only updated information with new insights and perspectives but also several new topics, such as a comprehensive discussion on biotic stressors, AMF interaction with other microorganisms, non-host plant species, plant secondary metabolism, signaling events in plant-AMF symbiosis, AMF-mediated nutrient acquisition and subsequent stress tolerance. The book also discusses the potential implications of AMF for sustainable crop production in the context of climate change. The book can be a useful reference book for academics and scientists involved in related research, such as academics in agronomy and plant sciences, scientists involved in beneficial fungi research, chemists, industrialists, and employees involved in the production and marketing of biofertilizers, master and doctoral degree students of agronomy, horticulture, and plant protection, consultants working on the production of crops in marginal environments as well as environmental scientists working for assisted phytoremediation programs. It would also be suitable for agronomy, ecology, and plant science-related courses, such as plant stress physiology, plant growth-promoting microbes, and plant pathology to teach undergraduate, graduate, and postgraduate students at colleges and universities.
Chapter 1. Introduction to arbuscular mycorrhizal fungi: characteristics, functions, and applications -- Chapter 2. Non-host plant species: definition, description and mechanisms of interaction with arbuscular mycorrhizal fungi -- Chapter 3. Interactions between arbuscular mycorrhizal fungi and other microorganisms in the rhizosphere and hyphosphere -- Chapter 4. Signaling events during the establishment of symbiosis between arbuscular mycorrhizal fungi and plant roots -- Chapter 5. Arbuscular mycorrhizal fungi and plant secondary metabolism -- Chapter 6. Arbuscular mycorrhizal fungi in acquisition of essential plant nutrients and mitigation of nutrient deficiency -- Chapter 7. Mechanisms of arbuscular mycorrhizal fungi-induced drought stress amelioration in plants -- Chapter 8. Arbuscular mycorrhizal fungi in plant tolerance to organic pollutants -- Chapter 9. Managing foliar diseases of crop plants by beneficial arbuscular mycorrhizal fungi -- Chapter 10. Applications of arbuscular mycorrhizal fungi in controlling root-knot nematodes -- Chapter 11. Glomalin and carbon sequestration in terrestrial ecosystems -- Chapter 12. Arbuscular mycorrhizal fungi in organic versus conventional farming -- Chapter 13. Arbuscular mycorrhizal fungi under intercrop and crop rotation systems -- Chapter 14. Arbuscular mycorrhizal fungi applications for sustainable agricultural systems.
Keywords: Fungi; Mycology; Microbiology; Agronomy; Botany; Plant physiology; Fungi; Agronomy; Plant Science; Plant Physiology